PERLINDUNGAN SUNGAI SEBAGAI RUANG EKOLOGIS PUBLIK DALAM PENEGAKAN TINDAK PIDANA LINGKUNGAN - Muhammad Dhobit Azhary Lubis; Silitonga, Saritua (Jurnal Perspektif Hukum, 2025)
Rivers constitute public ecological spaces that play a strategic role in environmental sustainability and in fulfilling the public’s right to a good and healthy environment. However, in practice, rivers in Indonesia continue to face serious threats from pollution and environmental degradation caused by human activities that are not yet effectively addressed through environmental criminal law enforcement. This study aims to analyze the protection of rivers as public ecological spaces within the framework of environmental criminal law enforcement and to assess its contribution to the fulfillment of the right to a healthy environment. This research employs a normative legal research method using statutory, conceptual, and case-based approaches, particularly through the analysis of court decisions related to river pollution. The findings indicate that, normatively, environmental regulations provide an adequate legal foundation for river protection; nevertheless, their implementation remains constrained by challenges in evidence gathering, the application of corporate criminal liability, and inconsistencies in sentencing practices. The study further reveals that the integration of environmental criminal law enforcement with an ecological restorative approach has significant potential to strengthen river protection and promote ecological recovery. Therefore, this research emphasizes the importance of reinforcing environmental criminal law enforcement as a strategic instrument to safeguard rivers as public ecological spaces and to ensure the public’s right to a good and healthy environment.